Preventing Anastomotic Leakage, a Devastating Complication of Colorectal Surgery - Hyun Gu Lee (The Ewha Medical Journal)
Anastomotic leakage (AL) after colorectal surgery is a significant concern, as it can lead to adverse functional and oncologic outcomes. Numerous studies have been conducted with the aim of identifying risk factors for AL and developing strategies to prevent its occurrence, thereby reducing the severe morbidity associated with AL. The intraoperative method for reducing AL includes a mechanical assessment of AL, an assessment of bowel perfusion, drain placement, and the creation of diverting stomas. The anastomosis technique is also associated with AL, and the appropriate selection and accurate application of anastomotic methods are crucial for preventing AL. Indocyanine green fluorescence imaging has recently gained popularity as a method for assessing bowel perfusion. While it is useful for detecting bowel perfusion, standardized protocols and measurement methods need to be established to ensure its reliability and effectiveness in clinical practice. The use of intraoperative drains to reduce AL has produced inconsistent results, and the routine adoption of this practice is not currently recommended. Diverting stomas can be used to help reduce the morbidity associated with AL. However, it is important to carefully consider the complications that can arise directly from the stoma itself. It should be noted that while a stoma can reduce AL, it cannot completely prevent it. This descriptive review examines various intraoperative methods aimed at reducing AL, discussing their effectiveness in reducing AL.